Relationship between abnormal pelvic floor electromyography and obstetric factors in postpartum women: a cross-sectional study - Juan Jiang; Chun Li; He-Yu Liu; Zheng-Yan Zhu (BMC, 2024)
Abstract Objective To evaluate the surface electromyography (sEMG) of pelvic floor muscles (PFMs), compare between vaginal birth and cesarean section and correlate with maternity and obstetrics characteristics in primiparous 6-8 weeks postpartum. Methods PFMs surface electromyography screening data of primiparous postpartum women in our hospital at 6-8 weeks postpartum from 2018 to 2021 were selected and analyzed. The study collected data on delivery activities of 543 postpartum women totally. Results In general, the abnormal incidence of pelvic floor electromyography in postpartum women mainly occurred in slow muscle (type I fiber) stage and endurance testing stage. Compared to vaginal birth postpartum women, the incidence of abnormal pelvic floor electromyography in cesarean section postpartum women is lower. There were statistical differences in measurement values of pelvic floor electromyography in several different stages between cesarean section and vaginal birth (P < 0.005). Regarding the influence on pelvic floor electromyography, there were more influencing factors on vaginal birth postpartum women including age, height, weight, weight gain during pregnancy, gestational week, and first and second stage of labor than on cesarean section postpartum women whose influencing factors included age, weight gain during pregnancy, and newborn weight. Conclusion Effects on surface electromyography (sEMG) of pelvic floor muscles (PFMs) at 6-8 weeks postpartum differed based on the different modes of delivery. The high-risk obstetric factors closely related to abnormal surface electromyography (sEMG) of pelvic floor muscles (PFMs) were maternal age, height, weight, and second stage of labor.